Public relations profile: report on Malaysian Practitioners 2018 - Syed Abdullah Idid, Syed Arabi; Ahmad, Zeti Azreen (Department of Communication, AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
The PR profile 2018 is the fifth report on the PR practitioners in Malaysia. Previous studies were conducted in 1977, 1992, 2003, and 2011. This report illustrates the current development of PR practitioners in Malaysia specifically on the following areas : -The demographic profile of practitioners -The roles of practitioners -The ethical values and professionalism -Job satisfaction -Social media usage -PR and crisis management -PR and corporate social responsibility